Acute Inflammatory Edema: A Case Report with Histopathological and Immunohistochemical Findings - Chirasuthat P; Chirasuthat S; Suchonwanit P (Dove Medical Press, 2021)
Phatcharawat Chirasuthat, Suthep Chirasuthat, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat SuchonwanitDivision of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, ThailandTel +66-2-2011141Fax +66-2-201-1211 ext 4Email poonkiat@hotmail.comAbstract: Acute inflammatory edema (AIE) is a rare variant of pseudocellulitis characterized by blanchable, erythematous, and edematous plaques mainly on the thighs and abdomen and sparing areas of increased pressure. The condition occurs predominantly in critically ill patients with hypoalbuminemia, those with increased body mass index, and those with evidence of fluid overload. AIE was introduced in 2019; however, its histopathological picture has never been elucidated in the literature. We report a case of AIE in a 64-year-old Thai woman with several comorbidities and illustrate its histopathological and immunohistochemical features for the first time. Treatment with diuretics, fluid restriction, and adjuvant hemodialysis revealed marked improvement after ten days. Our report emphasizes that AIE is a distinct dermatosis with specific characteristics that help differentiate AIE from cellulitis and other pseudocellulitic conditions. Furthermore, our observations support the role of lymphatic alterations in the pathogenesis of the disease.Keywords: cellulitis, dermis, edema-phage, lymphedema, pseudocellulitis, volume overload